Aplikasi Absensi Pembelajaran Siswa Paket C pada PKBM Tjiliwoeng Berbasis Android - Rifkiansyah, Bagas (Jurnal Ilmu Komputer; Vol 17 No 2 (2024): Jurnal Ilmu Komputer, 2024)
The rapid development of information technology has had a significant impact on various sectors, including education. Using a manual attendance system to record attendance data is vulnerable to data manipulation, and the attendance check system. This can be a problem, because it can make it difficult to collect and record attendance data, as well as time-consuming which can hinder the process of collecting authenticity from student attendance data. The author uses the RAD software development method (Rapid Application Development). Methods RAD (Rapid Application Development) has a focus on fast application development, using an object-oriented approach (Rahardiyanto & Alfatiha, 2022). Based on the results of research conducted by the author, in carrying out the process of designing an attendance application for package c student learning at PKBM Tjiliwoeng based on Android using technology Geolocation. Making it easier for PKBM Tjiliwoeng students not to need to be absent manually. Enough with this attendance application, students can make attendance easily at smartphone themselves. In the process of making this application, my absence still has drawbacks, namely that this application can only be run on smartphone with the Android operating system. The author hopes that this application can run on various operating systems, such as the iOS operating system, and so on.